Photoluminescence and refractive index dispersion properties of ZnO nanofibers grown by sot-gel method - Serbetci, Z.; El-Nasser, H. M.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2012)
Zinc oxide thin film was grown on glass substrate using sal gel spin coating method. The optical constants and dispersion energy parameters of the zinc oxide thin film were determined using optical characterization method. The optical band gap of the n-type ZnO semiconductor was found to be 3.24 eV. The refractive index dispersion of the ZnO obeys the single oscillator model. The dispersion energy and oscillator energy values of the ZnO film were found to be 13.74 eV and 6.61 eV, respectively. The real and imaginary parts of the dielectric constant of the ZnO film were determined. The photoluminescence spectra of the ZnO film indicate a peak around 401 nm (3.10 eV) due to the electron transition from the energy level of interstitial Zn to valance band and the another peak is observed around 530 nm (2.34 eV) which is attributed to the oxygen vacancies in ZnO. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ZnO semiconductor; Optical constants; Single oscillator model